Development and characterization of sulfonated polysulfone for membrane fuel cell - Wan Muhd Nadzmi, Wan Yaakub (2009)
Sulfonation process was used to produce ion exchange polymer from a commercial polysulfone .Membranes obtained from the sulfonated polysulfone (SPSU) are potential substitutes for perflourosulfonic acid membrane (NafionTM) used now in polymer electrolyte fuel cell due to its high cost to produce, needs of high pressure and high hydration level to operate effectively. Sulfonations were achieved by varying the degree of sulfonation (DS) in reaction time. Characterizations of different degree of sufonated polysulfone membranes were conducted through elemental analysistal, Fourier Transform Infared (FTIR) and swelling test. Fourier Transform Infared (FTIR) were used to confirm the presence of sulfonic group in the polymer after sulfonation process and it was clearly confirmed by the SO3 stretching bond at frequency 1020 cm-1 to 1035cm-1. The hydration levels of membrane were measured via swelling test. Result showed the percentages of water and methanol uptake broadening as the degree of sulfonation increased.